Guidelines of the Association of Anesthesiologists-Intensivists, the Interregional Non-Governmental Organization Alliance of Clinical Chemotherapists and Microbiologists, the Interregional Association for Clinical Microbiology and Antimicrobial Chemotherapy (IACMAC), and NGO Russian Sepsis Forum Diagnostics and antimicrobial therapy of the infections caused by multiresistant microorganisms - V. B. Beloborodov; V. G. Gusarov; A. V. Dekhnich; M. N. Zamyatin; N. A. Zubareva; S. K. Zyryanov; D. A. Kamyshova; N. N. Klimko; R. S. Kozlov; V. V. Kulabukhov; Yu. S. Polushin; V. A. Rudnov; et al. (Вестник анестезиологии и реаниматологии, 2020)
Introduction. Strains of microorganisms resistant to antimicrobial agents are commonly found in medical units throughout most regions of the world, including Russia. This leads to lower antimicrobial therapy efficacy when treating nosocomial infections. In this regard, the timely implementation of adequate antibiotic therapy is of great importance.The objective of the guidelines: To provide summarized information on contemporary approaches to microbiological diagnostics and the assessment of results, as well as the principles of rational use of antimicrobial and antifungal agents, including treatment of infections caused by multiple drug-resistant strains of microorganisms.Subjects and methods. These guidelines are based on published data obtained in the course of randomized trials, as well as information presented in the provisions of international guidelines supported by high-level evidence. The guidelines were prepared by a working group of Russian experts with extensive experience in research and practical work in this area. On October 11, 2019, the ﬁnal version of the guidelines was reviewed and approved at a joint meeting of the working group and representatives of the public organizations which initiated the development of these guidelines (Association of Anesthesiologists-Intensivists, the Interregional Non-Governmental Organization Alliance of Clinical Chemotherapists and Microbiologists, the Interregional Association for Clinical Microbiology and Antimicrobial Chemotherapy (IACMAC), NGO Russian Sepsis Forum).Conclusion. The guidelines reﬂect an interdisciplinary consensus of approaches to the diagnostics and antibiotic therapy of infections caused by multiresistant microorganisms. The provisions set forth should be used to decide on the strategy of empirical and etiotropic therapy of the most severe infections.